2002
DOI: 10.1007/s00442-002-0924-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of trichomes by three herbivores of black mustard

Abstract: Specificity of plant induction responses may be important to the interactions between mustards and insect herbivores. This study compared the effects of the cabbage white butterfly, Pieris rapae (L.), cabbage looper, Trichoplusia ni (Hubner), and the mustard flea beetle, Phyllotreta cruciferae (Goeze) on induction of leaf trichome density, sinigrin concentration, and nitrogen concentration in black mustard, Brassica nigra (L.) Koch. Plants were damaged for 12 h at the four-leaf stage, with effort made to stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 56 publications
(75 reference statements)
2
102
0
Order By: Relevance
“…This observation is in accordance with the observation of Copetta et al and Kapoor et al, [12,27] . Trichomes are important structural barrier component of resistance and glandular trichomes are sites for accumulation of secondary metabolites [48] . Increase in foliar tissue density indicates induction of systemic resistance in mycorrhizal plants.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in accordance with the observation of Copetta et al and Kapoor et al, [12,27] . Trichomes are important structural barrier component of resistance and glandular trichomes are sites for accumulation of secondary metabolites [48] . Increase in foliar tissue density indicates induction of systemic resistance in mycorrhizal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Wound-induced trichome formation has been reported in many plant species from diverse phylogenetic clades (Myers and Bazely, 1991;Agrawal, 1999;Traw and Dawson, 2002;Boughton et al, 2005;Holeski, 2007). It is known that the Myb-bHLH-WD40 complex is an evolutionarily conserved regulator of trichome development in Brassicaceae and Malvaceae, both of which belong to the Eurosid II clade of angiosperms (APG, 2003;Wang et al, 2004;Humphries et al, 2005;Gruber et al, 2006).…”
Section: Evolutionary Perspectivesmentioning
confidence: 99%
“…3,4,5 Acclimation occurs both on the biochemical and morphological level, e.g., by increasing defence compounds, 6 by synthesizing defence related proteins, by emitting volatiles to attract predators and parasites of herbivores 7 and by altering plant morphology via increased formation of trichomes, thorns or scleromorphy. 8,9 Many studies demonstrated resource based trade-offs between growth and defence on a large time scale (e.g. refs.…”
mentioning
confidence: 99%